Knowledge, Attitude, and Practice (KAP) of Pharmacovigilance among the different categories of frontline Covid-19 healthcare workers in a tertiary care hospital in West Bengal, India - Arijit Ghosh; Sangeeta Ghosh; Abhik Saha; Sabnam Ara Begum; Romit Chattaraj; Tapas Bera (International Journal of Health and Clinical Research, 2022)
Background: In these difficult times of Covid19 pandemic, there are rampant increase in uses of new/ old drugs which are approved or waiting to be approved or repurposed with a different dose and schedule to treat and prevent the disease. Information regarding ADRs are lacking for those drugs. Hence the need for ADR reporting by frontline Health Care Workers (HCW) are reemphasized to generate data regarding ADRs of these drugs. That’s why this study was required to evaluate the status of Knowledge, attitude & practice (KAP) of HCWs regarding ADR reporting and to plan steps to improve if found not sufficient. Materials & Methods: A hospital-based cross sectional pretested close ended questionnaire-based observational study was carried out in-inpatient departments (IPD), outpatient department (OPD) & Pharmacy Department of RG Kar Medical College & Hospital, Kolkata aimed at evaluating KAP regarding ADR reporting in different categories of frontline Covid-19 HCWs. Results: About 138 HCWs participated in the study after properly filling up informed consent form. Data collected and analyzed to find out that there was inadequate knowledge in about half of the participants (47.1%) & poor practice regarding ADR reporting. Only 22.5% HCWs encountered & reported ADRs. But there was no lack of favorable attitude regarding ADR reporting (84.78%). Conclusion: These findings indicate that proper encouragement and appropriate steps by administration can reverse the status of knowledge practice regarding ADR reporting.